Acute and Chronic Changes in Platelet Volume and Count After Cardiopulmonary Bypass Induced Thrombocytopenia in Man - Martin, J F; Daniel, T D; Trowbridge, E A (Thrombosis and Haemostasis, 1987)
Patients undergoing surgery for coronary artery bypass graft or heart valve replacement had their platelet count and mean volume measured pre-operatively, immediately post-operatively and serially for up to 48 days after the surgical procedure. The mean pre-operative platelet count of 1.95 ± 0.11 × 1011/1 (n = 26) fell significantly to 1.35 ± 0.09 × 1011/1 immediately post-operatively (p <0.001) (n = 22), without a significant alteration in the mean platelet volume. The average platelet count rose to a maximum of 5.07 ± 0.66 × 1011/1 between days 14 and 17 after surgery while the average mean platelet volume fell from preparative and post-operative values of 7.25 ± 0.14 and 7.20 ± 0.14 fl respectively to a minimum of 6.16 ± 0.16 fl by day 20. Seven patients were followed for 32 days or longer after the operation. By this time they had achieved steady state thrombopoiesis and their average platelet count was 2.44 ± 0.33 × 1011/1, significantly higher than the pre-operative value (p <0.05), while their average mean platelet volume was 6.63 ± 0.21 fl, significantly lower than before surgery (p <0.001). The pre-operative values for the platelet volume and counts of these patients were significantly different from a control group of 32 young males, while the chronic post-operative values were not. These long term changes in platelet volume and count may reflect changes in the thrombopoietic control system secondary to the corrective surgery.
Keywords: Platelet count; Platelet volume; Acute thrombocytopenia; Cardiopulmonary bypass